Food habits of the Freckled Duck and associated waterfowl in North-western New South Wales - Briggs, S V (Wildfowl, 1982)
Dietary habits of Freckled Duck Stictonetta naevosa, Pink-eared Duck Malacorhynchus membranaceus and Australian Grey Teal Anas gibberifrons gracilis were investigated at Fort Grey Basin in north-western New South Wales, Australia. On the basis of their oesophagus contents, Freckled Duck fed mainly on ostracods (53.0%) and Portulaca seeds (20.3%), Pink-eared Duck mainly on Micronecta (30.4%), microcrustaceans (25.7%), and chironomid larvae (20.0%), and Grey Teal mainly on Micronecta (43.7%), other corixids (16.1%) and Polygonum seeds (16.1 %). The three species of waterfowl fed by different means and appeared to favour different zones. Gizzards from the three species contained markedly lower proportions of animal foods, than did their oesophagi. In these three species of Australian waterfowl, invertebrates formed a larger part of the diet than previous gizzard studies have indicated.